Keratinocyte growth factor attenuates lung leak induced by alpha-naphthylthiourea in rats - Mason, C M; Guery, B P; Summer, W R; Nelson, S (Critical care medicine, 1996)
To investigate the effect of pretreatment with keratinocyte growth factor on acute permeability pulmonary edema. Prospective, randomized, controlled animal study. University research laboratory. Specific pathogen-free Sprague-Dawley rats. Acute permeability pulmonary edema was induced with an injection of alpha-naphthylthiourea, and lung leak was assessed in an isolated perfused lung model over 180 mins. Leak was confirmed with wet/dry lung weight ratios, and the alveolar fluid protein concentration was measured after bronchoalveolar lavage. The effect of pretreatment with keratinocyte growth factor (injected intratracheally 48 hrs before the experiment) on alpha-naphthylthiourea-induced pulmonary edema was assessed (keratinocyte growth factor/alpha-naphthylthiourea group). Control groups (Control and keratinocyte growth factor/Control) were also studied. Histopathology was performed for each of the four groups. The alpha-naphthylthiourea produced an acute permeability pulmonary edema detected by lung leak over the 180-min ex vivo period of monitoring the isolated perfused lung (leak = 8+/-mL; wet/dry weight ratio 14.7+/-2; lavage protein 3.1+/-1 mg/mL). Pretreatment with keratinocyte growth factor significantly attenuated these parameters (leak = 2.3+/-0.4 mL; wet/dry weight ratio 7.1 +/- 0.5; lavage protein 0.28 +/-0.03 mg/mL), which were not significantly different from the control group and the keratinocyte growth factor/control group. Histopathology showed abundant type II pneumocyte hyperplasia in the lungs of animals pretreated with keratinocyte growth factor, and marked pulmonary edema in animals pretreated with alpha-naphthylthiourea. Less edema was apparent in the keratinocyte growth factor/alpha-naphthylthiourea group. All data are expressed as mean +/- SEM. Pretreatment with keratinocyte growth factor significantly attenuates pulmonary edema induced by alpha-naphthylthiourea. The mechanisms of this protection are likely related to type II pneumocyte hyperplasia, but remain to be specifically elucidated.